Phylogenetic Analysis of Klebsiella pneumoniae Isolated from Nosocomial and Community Infection in Diyala, Iraq - Mohamed, Ibtihal Qasim; Al-Taai, Hadi Rahman Rasheed (Iraqi Journal of Science, 2023)
The biological diversity of Klebsiella pneumoniae (K. pneumoniae) has widely been reported to be associated with pathological progress in severe nosocomial and community-acquired infections. 250 clinical specimens included sputum, urine and swabs from wound and burns samples were collected from Al-Batool Teaching Hospital (38.4%), Baqubah Teaching Hospital (61.6%) and private laboratories in Baqubah and Diyala, Iraq. Positive rates of nosocomial acquired infection were sputum 98%, urine 96%, and swabs from wound and burns 94%, while positive rates of community acquired infection were sputum 60%, urine 60%, and swabs wound and burns 30%. Positive rates of nosocomial and community acquired infections were 96% and 48%, respectively. The distribution of pathogenic bacteria of E. coli was 19.2% and 8.8%, and those of K. pneumoniae were 23.2% and 12% of nosocomial and community acquired infections respectively, which is a higher percentage than other pathogenic bacteria of nosocomial and community acquired infections. The nosocomial-acquired K. pneumoniae isolates were less susceptible than community-acquired K. pneumoniae isolates. Multi-drug resistant (MDR) and extensively drug resistant (XDR) are commonly caused by -lactam/ -lactamase inhibitor combinations: Ticarcillin clavulanate, carbapenems and meropenem 100%; cephalosporines and ceftazidime 96%. Phylogenetic analysis of the 16S rRNA gene showed the presence of six nucleic acid variations in various samples. This variance might exhibit a clear tendency to be localized in the community acquired K. pneumoniae isolates. Fifteen ribosomal sequences were deposited at GenBank in accession numbers starts from OM992298 to OM992312.